Field Survival of the Brown Marmorated Stink Bug Halyomorpha halys (Hemiptera: Pentatomidae) on California Tree Crops. Issue 5 (27th June 2021) - Stahl, Judith M; Scaccini, Davide; Daane, Kent M
Abstract: Halyomorpha halys (Stål) (Hemiptera: Pentatomidae) is a polyphagous insect pest that has invaded much of the United States, including California. Despite model predictions that regions in California like the agriculturally important Central Valley are suitable, H. halys populations and the occurring crop damage are distinctly lower than in regions of the East Coast. To evaluate if this is due to low nymphal survival in the high temperature and intensive monoculture environment, H. halys nymphs were caged on four common Central Valley tree crops: almond, pistachio, peach, and grape, and compared to the well-established almond and pistachio pest Leptoglossus zonatus (Dallas) (Hemiptera: Coreidae). Nymphal development showed that peach, almond, and pistachio can sustain H. halys as single host plants until adult eclosion, whereas grapes cannot. The addition of fruiting structures of almond, pistachio, and grape to H. halys caged on peach trees (= mixed diet) did not increase nymphal survival but did increase adult female size. Leptoglossus zonatus survival was higher than H. halys on pistachio, but not on the other crops. Overall, H. halys nymphal mortality in the field was high, with 92% in the mixed diet compared to 73% in the mixed diet control in the laboratory, indicating abiotic population pressures. Our results confirm peach as a good H. halys host plant and suggest that almond has a similar suitability, and while pistachios can support H. halys nymphal development, they seem less likely to facilitate population growth.